2001
DOI: 10.1021/bm0001493
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrophobins HFBI and HFBII from Trichoderma reesei Showing Efficient Interactions with Nonionic Surfactants in Aqueous Two-Phase Systems

Abstract: Fungal hydrophobins are a group of surface active, self-assembling proteins. The filamentous fungus Trichoderma reesei produces two (class II) hydrophobins, HFBI and HFBII. We have studied how these water-soluble hydrophobins behave in two-phase systems using a series of nonionic surfactants with different characteristics. It was found that both hydrophobins, but especially HFBI, had a very high affinity for the surfactants. The highest partitioning coefficient, over 2500, was observed for HFBI with C(11)EO(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 37 publications
4
119
0
Order By: Relevance
“…Firstly, it has been shown that fusion of a foreign protein with a secreted native protein can enhance its production (e.g. Nyyssönen et al, 1993), and secondly, HFBI as a fusion partner can facilitate the purification of recombinant proteins in aqueous two-phase purification (Linder et al, 2001;Selber et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it has been shown that fusion of a foreign protein with a secreted native protein can enhance its production (e.g. Nyyssönen et al, 1993), and secondly, HFBI as a fusion partner can facilitate the purification of recombinant proteins in aqueous two-phase purification (Linder et al, 2001;Selber et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46] Fluorolink F10 (F10/A-ammonium salt, F10 in the text) was obtained from Solvay Specialty Polymers (Italy). The reagents (octadecylmercaptan, dodecane, ethylene glycol, diiodomethane) and solvents ( n -hexane, 2-propanol, and methanol) were purchased from Sigma-Aldrich and used without further purifi cation.…”
Section: Methodsmentioning
confidence: 99%
“…It is a recombinant chimeric protein consisting of two CBDs from T. reesei, which preparation is described by Linder et al [26]. To the N terminus of this construct the hydrophobin protein HFBI also from T. reesei was fused in order to facilitate the protein purification [27]. The sequence of the HFBI tag is: SNGNGNVCPP GLFSNPQCCA TQVL-GLIGLD CKVPSQNVYD GTDFRNVCAK TGAQPLC-CVA PVAGQALLCQ TAVGA.…”
Section: Cbd Samplesmentioning
confidence: 99%
“…The protein was produced in T. reesei using the cbh1 promoter. The protein was purified from the culture supernatant using the HFBI tag by surfactant extraction as described in [27]. Briefly, 2% Berol 532 (Akzo-Nobel, Sweden) was added to the supernatant.…”
Section: Cbd Samplesmentioning
confidence: 99%